The Effects of p-nonylphenol on the Myometrial Contractile Activity - Yasemin Özatik, F.; Kaygısız, B.; Erol, K.; Dündar, Y.; Önkol, T.; Şahin, M. F. (Drug Research, 2015)
We aimed to investigate the effects and mechanisms of action of p-nonylphenol(p-NP) on uterine contractility in rats. The uterine tissues of female Sprague Dawley rats in diestrus were bathed in isolated organ bath. The effects of vehicle alone (0.1% ethanol), the positive control 17-β-E2 (10−5 M) and p-NP (10−9 M, 10−8 M, 10−7 M, 10−6 M) on spontaneous and KCl-induced uterine contractility of rats were studied. Also, the effects of p-NP in combination with actinomycin D (10−5 M) (gene transcription inhibitor), cycloheximide (10−4 M) (protein synthesis inhibitor), fulvestrant (10−6 M) (pure estrogen receptor antagonist), 2-hydroxy-5-nonanoylbenzamide (10−3 M) (compound 1b, anti-uterotrophic compound) on spontaneous uterine contractions, and with propranolol (20 µM) (β-adrenoceptor antagonist) and noradrenaline (5 µM) on KCl (40 mM) induced contractions were investigated. p-NP exhibited a concentration-dependent inhibition on spontaneous uterine contractions. There was no significant difference between the highest p-NP concentration (10−6 M) and the positive control 17-β-E2 in terms of % inhibition (p>0.05). The inhibitory effect of p-NP (10−6 M) on spontaneous contractions was blocked by actinomycin D (p<0.001), cycloheximide (p<0.001), fulvestrant (p<0.001) and compound 1b (p<0.001). 17-β-E2 (10−5 M) exerted a higher inhibition % on KCl induced contractions than p-NP (10−6 M). The relaxant effect of p-NP on KCl-induced uterine contractions was inhibited by noradrenaline (p<0.05) but not by propranolol (p>0.05). We suggest that p-NP inhibited uterine contractions similar as 17-β-E2 and genomic pathways are involved and β-adrenoceptors might modulate the activity of p-NP. In addition, compound 1b showed an uterotonic activity and reversed the effect of p-NP.
Keywords: 2-hydroxy-5-nonanoylbenzamide; isolated organ bath; p-nonylphenol; uterine contractility